2020
DOI: 10.1055/s-0040-1708834
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Postoperative Pain Control in Autologous Breast Reconstruction: A Systematic Review

Abstract: Background Pain management approaches in autologous breast reconstruction have become a topic of great interest in the era of enhanced recovery after surgery protocols, as well as the opioid epidemic. The management of postoperative pain is of critical importance for women undergoing breast reconstruction; however, these protocols have yet to be synthesized and compared in the primary literature. Herein, we present a systematic review of approaches to provide optimal pain control while minimizing narcotic use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…26 Each modality of an ERAS protocol plays an important role in patients' recovery, and in the case of ketorolac, some treatments can be synergistic in controlling postoperative pain without reliance on opiates. While ERAS protocols can be beneficial in decreasing postoperative opiate utilization, 23 not every institution has implemented formal ERAS protocols. For those institutions, gabapentin and Lyrica can be helpful alternatives to ketorolac for postoperative pain control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Each modality of an ERAS protocol plays an important role in patients' recovery, and in the case of ketorolac, some treatments can be synergistic in controlling postoperative pain without reliance on opiates. While ERAS protocols can be beneficial in decreasing postoperative opiate utilization, 23 not every institution has implemented formal ERAS protocols. For those institutions, gabapentin and Lyrica can be helpful alternatives to ketorolac for postoperative pain control.…”
Section: Discussionmentioning
confidence: 99%
“…A multiple linear regression was created to assess the association of different variables that have been shown to affect postoperative pain (BMI, bilateral reconstruction, concurrent mastectomy, ketorolac use, and other NSAIDs including celecoxib and ibuprofen) with MMEs per day. 22,23 Because of the wide distribution of opiate use among the two cohorts, we also split each cohort into tertiles (low, medium, and high users) based on MMEs/day for comparison. Continuous variables were compared using the Kruskal-Wallis test, while categorical variables were compared using Pearson chi-squared and Fisher's exact tests where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…However, many of these studies focus on the abdominal donor site (for autologous breast reconstruction), rather than the breast and chest wall, and many only report on ERAS efficacy for acute pain management, rather than long-term neuropathic pain. 32 34 …”
Section: Pmps Treatmentmentioning
confidence: 99%
“…However, many of these studies focus on the abdominal donor site (for autologous breast reconstruction), rather than the breast and chest wall, and many only report on ERAS efficacy for acute pain management, rather than long-term neuropathic pain. [32][33][34] Gabapentin has also been shown to reduce immediate postoperative pain following mastectomies and other breast surgeries, and is often a component of ERAS protocols. 35,36 In their randomized control trial, Fassoulaki et al found that combining perioperative gabapentin and local anesthesia led to a significant decrease in chronic pain 3 months after surgery, supporting the importance of a multimodal approach to preventing PMPS.…”
Section: Prevention Of Pmps/pbspsmentioning
confidence: 99%
“…[17][18][19] In a systematic review of 28 studies examining pain management for breast reconstruction, opioid consumption was reduced in all seven studies that included ERP protocols and in eight of nine studies that included TAP or paravertebral blocks. 20 In this systematic review, liposomal bupivacaine, a formulation of the local anesthetic bupivacaine enabling controlled release of bupivacaine for prolonged analgesia, was highlighted for pain management after breast reconstruction. 20 Previous studies investigated liposomal bupivacaine administered as a TAP block (including as part of an ERP protocol) for DIEP flap breast reconstruction, [15][16][17][21][22][23] with some showing reduced opioid consumption versus historical controls.…”
Section: Introductionmentioning
confidence: 99%